Improved distances and ages for stars common to TGAS and RAVE - McMillan, Paul J.; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. We combine parallaxes from the first Gaia data release with the spectrophotometric distance estimation framework for stars in the fifth RAVE survey d